2022
DOI: 10.3390/polym14204429
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Properties and Mixing Mechanism of Rubber Asphalt Colloid for Sustainable Infrastructure

Abstract: Rubber asphalt has always been considered to have the most potential for the disposal of waste tires as sustainable infrastructure. However, the covalently cross-linked tire rubber presents an extreme challenge in reusing waste rubbers in roads. Rubberized asphalt with finely dispersed or colloidal structure has been regarded as a potential binder used as road material because of the improved properties in terms of storage stability, easy processing and high content of incorporation. However, the mixing mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 71 publications
0
2
0
1
Order By: Relevance
“…From Figure 5, it was observed that indirect tensile strength increased for mix M90-10 when compared to the reference mix M100-0, and for the remaining mix, ITS got reduced, while the indirect tensile strength ratio was higher than the desirable ITS ratio of 0.8 [21]. The indirect tensile strength of asphalt mixes decreases with the inclusion of polymers contained in asphalt, possibly because the polymers act as plasticizers [22]. The intermolecular forces between the asphalt molecules make the asphalt more pliable and less susceptible to fracture [23,24].…”
Section: Indirect Tensile Strength and Moisture Sensitivitymentioning
confidence: 95%
“…From Figure 5, it was observed that indirect tensile strength increased for mix M90-10 when compared to the reference mix M100-0, and for the remaining mix, ITS got reduced, while the indirect tensile strength ratio was higher than the desirable ITS ratio of 0.8 [21]. The indirect tensile strength of asphalt mixes decreases with the inclusion of polymers contained in asphalt, possibly because the polymers act as plasticizers [22]. The intermolecular forces between the asphalt molecules make the asphalt more pliable and less susceptible to fracture [23,24].…”
Section: Indirect Tensile Strength and Moisture Sensitivitymentioning
confidence: 95%
“…Penelitian ini didasarkan pada metode deskriptif dengan melakukan penelaahan kebijakan dan prospek penggunaan aspal karet. Data penelitian didapat dari data sekunder antara lain seperti Badan Pusat Statistik (2021), Produksi Karet Menurut Provinsi di Indonesia (Produksi Karet Menurut Provinsi Di Indonesia , 2008-2012 Rubber Production by Province in Indonesia , 2008Indonesia , -2012Indonesia , , 2012 (Zhang et al, 2022;Suaryana & Sofyan, 2019;Ali et al, 2013;Abu Bakar et al, 2018;Karacasu et al, 2015;Blazejowski et al, 2018) yang menyatakan penerapan aspal karet dapat meningkatkan kualitas jalan, ketahanan jalan dan peningkatan umur jalan.…”
Section: Metode Penelitianunclassified
“…Most existing reviews on rubberized asphalt pavements focused on performance indicators such as permanent deformations, fatigue life, noise, and wear. However, various applications of ELT have not been compared and contrasted, nor have the ecological, health, and emission aspects been thoroughly examined. Accordingly, this paper reviews major studies relevant to rubber treatment technologies and the rejuvenation, health, economic, and environmental aspects of ELT in different applications, including but not limited to pavements.…”
Section: Introductionmentioning
confidence: 99%